Impact of COVID-19 pandemic on general surgical practice at tertiary care hospital in Pakistan - A single center analysis - Omema Saleem; Umm-e Habiba Abdul Rauf; Mujeeb Rehman Malik; Karim Rizwan Nathani; Faisal Ghani Siddiqui (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
The Coronavirus Disease 2019 (COVID-19) has adversely affected the global healthcare system, especially the management of surgical diseases. Most guidelines issued during pandemic recommended deferral of elective surgeries to decrease transmission and conserve resources for COVID-19 management, which raised the risk of complications. This study was conducted to evaluate the impact of the COVID-19 pandemic on the general surgical practice of a tertiary healthcare facility in Sindh, Pakistan. The data were retrospectively retrieved from the operation room records for most common general surgical procedures performed between January 2019 to December 2020 (i.e. peak COVID-19 restriction period). Monthly frequencies of the enrolled procedures were compared to COVID-19-associated incidence, recoveries, and mortality in Sindh. The six enrolled procedures suffered a reduction of 23.9% from 2019 to 2020. However, the difference was not significant (p >0.05) for the procedures collectively or individually, except for trucut biopsy (p =0.042). COVID-19-associated mortality significantly influences the frequency of the surgical procedures, compared to the pre-COVID era (p =0.042). However, the association was significant for the procedures collectively only, but in the individual procedure, only open inguinal hernia repair (p =0.011) showed a significant difference. In conclusion, there was a significant reduction in surgical cases with the potential risk of complications. Therefore in such situations, there must be a developed system to that the cases may be decided on an individual basis.